Perencanaan Overlay Jalan Kedungringin-Kedungboto Menggunakan Rigid Pavement Dan Flexible Pavement - A’isyah, Putri Dewi; Kusumaningsih, Dian (Jurnal Sains dan Teknologi (JSIT), 2025)
Roads are crucial infrastructure supporting public mobility and economic growth. Over time, road pavement structures deteriorate due to increased traffic volume and lack of maintenance. This study aims to design an overlay on the Kedungringin-Kedungboto Road section by comparing two types of pavement structures: rigid pavement and flexible pavement. The method used in this study refers to Pd-T-14-2003 for rigid pavements and the AASHTO 1993 method for flexible pavements, based on the 2017 or 2024 Road Pavement Design Manual (MDPJ). The data used include an Average Daily Traffic (LHR) of 600 vehicles/day, a CBR value of 5% for the subgrade, an assumed design life of 20 years, and the existing condition of the pavement structure. The calculation results using the AASHTO 1993 method obtained a Structural Number (SN) value of 2.8, which was then converted into a flexible pavement overlay layer with a total thickness of 10 cm, consisting of AC-BC (Base Course) and AC-WC (Wearing Course) layers. Meanwhile, the Pd-T-14-2003 method produced a concrete slab thickness of 20 cm, with stress and fatigue evaluation results indicating a working stress value (σ) of 3.75 MPa < concrete flexural strength (fₜ) of 4.5 MPa, and Df = 0.438 <1, thus the structure is declared safe from fatigue cracking. From the analysis results, flexible pavement is considered more economical in terms of initial costs, while rigid pavement has advantages in durability, design life, and resistance to repeated loads over a long period.